Study on Thermal Conductivity Methane Sensor Constant Temperature Detection Method - Ding Xibo; Guo Xiaoyan; Chen Yuechao; Sun Xue; Li Zhaoxia (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
The thermal conductivity methane sensor can detect methane concentration that measures the thermal conductivity coefficient of the measured methane different from the background gas. This sensor has advantages of detection of a variety of gases, large measuring range, stability, long working life, but also has defects, such as poor detection accuracy, sensitivity affected by ambient temperature and sensor temperature, the defect limits a wide applications of the sensor. This paper analyzes the theory of thermal conductivity methane sensor and method of measurement, proposes thermal conductivity methane sensor constant temperature detection method, and experimentally validates the feasibility of ambient temperature compensation. Experimental results show that the method effectively reduces the effect of ambient temperature on measuring accuracy.